Physical activity of parents and of their children: a systematic review of Brazilian sample studies - Report Card Brazil - William Rodrigues Tebar; Crystian Bitencourt Soares Oliveira; Fernanda Caroline Staquecini Gil; Bruna Thamyres Ciccoti Saraiva; Vinicius Yukio Botelho Suetake; Catarina Covolo Scarabottolo; Leandro Dragueta Delfino; Rômulo Araujo Fernandes; Diego Giulliano Destro Christofaro (Universidade Federal de Santa Catarina, 2018)
The aim of this study was systematically review the researches in regard the association of PA of parents and the PA of their children. A literature search was performed in five databases (Medline, Embase, Cinahl, Lilacs and SciELO) using combined terms about youth, PA and social support, with restriction to publications with Brazilian sample and to English and Portuguese language. Thirteen studies were included in this review and was observed a positive association of parental PA and the PA of their children for the majority of the studies (n=11). Only two studies did not observed significant association between PA of parents and their children and, otherwise, it was not observed negative associations in the review. It was observed different associations according to the gender of both parents and children. This findings support the importance for the practice of PA by parents as encouragement for the practice of PA by their children among Brazilians. The strategies to promote the increase in practice of physical activity of children and adolescents of both genders may consider the social support as an important factor, especially in relation to the practice of PA of their parents.